Assumed infectiousness, treatment adherence and sexual behaviours: applying the Swiss Statement on infectiousness to HIV‐positive alcohol drinkers. Issue 5 (29th October 2012) - Kalichman, SC; Grebler, T; Amaral, CM; McKerey, M; White, D; Kalichman, MO; Cherry, C; Eaton, L
<x xml:space="preserve">Abstract</x> Objectives The success of antiretroviral therapy (ART) for treating HIV infection is now being turned towards HIV prevention. The Swiss Federal Commission for HIV/AIDS has declared that HIV‐positive persons who are treated with ART, have an undetectable viral load, and are free of co‐occurring sexually transmitted infections (STIs) should be considered noninfectious for sexual transmission of HIV. This study examined the implications of these assumptions in a sample of HIV‐positive individuals who drink alcohol. Methods People living with HIV/AIDS (n = 228) were recruited through community sampling. They completed confidential computerized interviews and underwent monthly unannounced pill counts for ART adherence. HIV viral loads were obtained from medical records. Results One hundred and eighty‐five HIV‐positive drinkers were currently receiving ART and 43 were untreated. Among those receiving ART, one in three were not virally suppressed and one in five had recently been diagnosed with an STI. Adherence was generally suboptimal, including among those assumed to be less infectious. As many as one in four participants reported engaging in unprotected intercourse with an HIV‐uninfected partner in the past 4 months. There were few associations between assumed infectiousness and sexual practices. Conclusions Less than half of people who drank alcohol and took ART met the Swiss criteria for noninfectiousness. Poor adherence and prevalent STI threaten the long‐term potential of using ART for prevention. In the absence of behavioral interventions, the realities of substance use and other barriers call into question the use of ART as prevention among alcohol drinkers.